Functionality and Seniors: Where Are We and Where Should We Be Going? [Funcionalidade E Pessoas Idosas: Onde Estamos E Para Onde Devemos Ir?] [Funcionalidad y Personas Mayores: ¿Dónde Estamos y Hacia Dónde Ir?] - Villalobos-Dintrans, P (Pan American Health Organization, 2022)
The process of population aging will lead to an increase in health problems in older people, mainly related to their functionality. Accordingly, the countries of the Region of the Americas must begin to act to meet this challenge. One of the fundamental tasks involves the ability to measure and monitor functionality in the population. The tools used to evaluate functionality focus mainly on the basic activities of daily living, which limits their preventive capacity, since instrumental activities provide a better prognosis. Using the case of Chile, challenges for the Region were identified, mainly related to the advantages of adopting new methodologies that not only evaluate functional capacity, as current strategies do, but also detect its deterioration early and monitor its stages throughout the dependence stage in older people. This will also make it possible to evaluate initiatives for the prevention and management of loss of functionality. © 2022 Pan American Health Organization. All rights reserved.